Research on Ferromagnetic Hysteresis of a Magnetorheological Fluid Damper - Li, Zhaochun; Gong, Yao (Frontiers in Materials, 2019)
The inherent hysteresis of magnetorheological fluid dampers is one of the main reasons which limit their applications. The hysteresis mainly caused from two aspects. One part of the hysteresis is between the damping force and the piston velocity, which induced from the friction force of the damper, the compressibility of the fluid, rheological behavior etc. Another part of the hysteresis is between the damping force and the control current, which induced from the ferromagnetic materials inside the MR fluid damper. The ferromagnetic hysteresis of the MR fluid damper has been paid little attention to for a long time. Currently, the MR fluid damper is applying to the field of high velocity or shock and impact loadings where ferromagnetic hysteresis reduces the performance of the control current which leads to worse performances of vibration or buffer. Hall sensors are embedded to the MR fluid damper in this paper so that the magnetic flux density of the damping channels can be measured in real time. The hysteresis loops of the damping channels are obtained by measuring the relationships of the magnetic flux densities and the control currents. Furthermore, a Jiles-Atherton (J-A) hysteresis model based on differential equations for the MR fluid damper is established. The J-A hysteresis model is according to the domain-wall theory so that it has clear physical meaning with a small number of parameters. The hysteresis model is simulated utilizing MATLAB/SIMULINK. The particle swarm optimization (PSO) is adopted to identify the parameters of the J-A hysteresis model. The results show that the hysteresis loops identified by PSO is more similar to the measured hysteresis loops compared with the traditional parameter identification method. The research in this paper on the characteristic and model of the ferromagnetic hysteresis of the MR fluid damper is benefit to decrease or eliminate the effects of hysteresis which can improve the performances of the MR fluid dampers.